Cognitive and Emotional Appraisal of Motivational Interviewing Statements: An Event-Related Potential Study - Hui, Karen Y. L.; Wong, Clive H. Y.; Siu, Andrew M. H.; Lee, Tatia M. C.; Chan, Chetwyn C. H. (Frontiers in Human Neuroscience, 2021)
The counseling process involves attention, emotional perception, cognitive appraisal, and decision-making. This study aimed to investigate cognitive appraisal and the associated emotional processes when reading short therapists’ statements of motivational interviewing (MI). Thirty participants with work injuries were classified into the pre-contemplation (PC, n=15) or readiness stage of change group (RD, n=15). The participants viewed MI congruent (MI-C), MI incongruent (MI-INC), or control phrases during which their electroencephalograms were captured. The results indicated significant Group × Condition effects in the frontally oriented late positive complex (LPC). The LPC’s amplitudes were more positive-going in the PC than in the RD group for the MI congruent statements. Within the PC group, the amplitudes of the N400 were significantly correlated (r = 0.607-0.649) with the participants’ level of negative affect, . Our findings suggest that the brief contents of MI statements alone can elicit late cognitive and emotional appraisal processes beyond semantic processing.